Dabrafenib plus trametinib versus anti-PD-1 monotherapy as adjuvant therapy in BRAF V600-mutant stage III melanoma after definitive surgery: a multicenter, retrospective cohort studyResearch in context - Xue Bai; Ahmed Shaheen; Charlotte Grieco; Paolo D. d’Arienzo; Florentia Mina; Juliane A. Czapla; Aleigha R. Lawless; Eleonora Bongiovanni; Umberto Santaniello; Helena Zappi; Dominika Dulak; Andrew Williamson; et al. (EClinicalMedicine, 2023)
Summary: Background: Both dabrafenib/trametinib (D/T) and anti-PD-1 monotherapy (PD-1) are approved adjuvant therapies for patients with stage III BRAF V600-mutant melanoma. However, there is still a lack of head-to-head comparative data. We aimed to describe efficacy and toxicity outcomes for these two standard therapies across melanoma centers. Methods: This multicenter, retrospective cohort study was conducted in 15 melanoma centers in Australia, China, Germany, Italy, Japan, UK, and US. We included adult patients with resected stage III BRAF V600-mutant melanoma who received either adjuvant D/T or PD-1 between Jul 2015 and Oct 2022. The primary endpoint was relapse-free survival (RFS). Secondary endpoints included overall survival (OS), recurrence pattern and toxicity. Findings: We included 598 patients with stage III BRAF V600-mutant melanoma who received either adjuvant D/T (n = 393 [66%]) or PD-1 (n = 205 [34%]) post definitive surgery between Jul 2015 and Oct 2022. At a median follow-up of 33 months (IQR 21–43), the median RFS was 51.0 months (95% CI 41.0-not reached [NR]) in the D/T group, significantly longer than PD-1 (44.8 months [95% CI 28.5-NR]) (univariate: HR 0.66, 95% CI 0.50–0.87, P = 0.003; multivariate: HR 0.58, 95% CI 0.39–0.86, P = 0.007), with comparable OS with PD-1 (multivariate, HR 0.90, 95% CI 0.48–1.70, P = 0.75). Similar findings were observed using a restricted-mean-survival-time model. Among those who experienced recurrence, the proportion of distant metastases was higher in the D/T cohort. D/T had a higher incidence of treatment modification due to adverse events (AEs) than PD-1, but fewer persistent AEs. Interpretation: In patients with stage III BRAF V600-mutant melanoma post definitive surgery, D/T yielded better RFS than PD-1, with higher transient but lower persistent toxicity, and comparable OS. D/T seems to provide a better outcome compared with PD-1, but a longer follow-up and ideally a large prospective trial are needed. Funding: Dr. Xue Bai was supported by the Beijing Hospitals Authority Youth Programme (QMS20211101) for her efforts devoted to this study. Dr. Keith T. Flaherty was funded by Adelson Medical Research Foundation for the efforts devoted to this study.